Analisis Dampak Penerapan Sistem ERP terhadap Kinerja Pengguna - Wicaksono, Aries; Mulyo, Hery Harjono; Riantono, Ignatius Edward (Bina Nusantara University, 2015)
The background of this research was to determine how the impact of the implementation and use of ERP systems on user performance and the factors that affect the successful implementation of the ERP system so that it can have a positive impact for users of the ERP system after the implementation of ERP systems. This study aims to Knowing whether the implementation of ERP systems on firm performance impact on ERP users in the company and Produce conclusions in the form of an evaluation of the implementation of ERP in the company in order to provide a positive impact on user performance. The model used to evaluate the impact of the implementation of the ERP system is Quantity of Work, Quality of Work, Job Knowledge, Creativeness Cooperation, Dependability, Initiative, personal qualities. The method used in this research is descriptive qualitative method of analytical and evaluative, by analyzing the impact of the implementation of the ERP system to the components of the users performance. The results obtained are implementing ERP systems have a positive impact on user performance components.